ปัญหาการบังคับใช้กฎหมายกับหนังสือค้ำประกันที่ธนาคารพาณิชย์เป็นผู้ออก - เสาวภา เหล่าพลประทีป (จุฬาลงกรณ์มหาวิทยาลัย, 2015)
Letter of Guarantee is a service which Bank issues as guarantor for customers to comply their agreement or any obligation to other party. If customers don’t comply their agreement, Bank has to pay a loan for the beneficiary of a Letter of Guarantee. The purpose of this thesis is to study the laws concerning contracted agreements between the creditors, their debtors and the banks who are guarantors of the transactions in to all parties satisfaction. From initial studies, it was found that the laws enforced in the agreements do not align with prevailing laws negatively effecting the rights of all parties concerned for example the agreement at the end of each contract "when the bank has completed it’s responsibility as guarantor or when the letter of guarantee is past due, please return the original letter of guarantee to the bank". Banks often use this point against creditors in negating responsibility claiming that the debtor is fraudulent or that the creditor misunderstood by having returned the original letter of guarantee to the debtor instead of to the bank. This is why banks claim that they cannot pay the debtor. As the debtor returns the original letter of guarantee to the bank in order to withdraw his collateral, the banks have no recourse from the debtor resulting in damages to the bank. When the verdict is handed down, the bank has to take responsibility. Furthermore, from the application of the letter of guarantee, it is stipulated that the applicant is responsible to the bank for the debt incurred to the debtor and has no claim on the bank whatsoever. In case there is a way that cause the banks loss it right to recourse from the debtor under the guarantee laws. The point which shows in the application for Letter of Guarantee will use by the bank to claim for the debt from the applicant by the loophole of the law which make the bank to be the direct creditor under the law that not fair for the debtor. The undersigned proposes that banks should operate unambiguously with ethical governance in their dealings with their customers. Furthermore, there should be improvements in the practical application of the bank in strictly keeping track the expiries of the deals made. Furthermore, the letter of application should be made part of the letter of guarantee in order to correct the problem created by the loophole in the law which banks use as recourse in claiming the debt.